Indole-3-butyric acid immediately induced adventitious root of Dendrodium milla nayla x Dendrobium striaenopsis planted on coco-hust and wood charcoal - Tintrim Rahayu; Gatra Ervi Jayanti; Dita Agisimanto (The East Java Biological Society, 2022)
Orchids are one of the most favorite cut flowers, flowering potted plants, and have developed into a highly profitable industry. The development of acclimatization method is a necessity for the high survival rate of plantlets. The aim of this study was to investigate the effect of low indole-3-butyric acid (IBA) concentration on faster root formation of Dendrobium hybrid planted on coco- husk and charcoal in a short time. Plantlets derived from the seed culture of Dendrodium milla nayla x Dendrobium striaenopsis were harvested and pre-acclimated, planted on charcoal or coco-husk, and regularly sprayed with 0.25, 0.50, 0.75, and 1.0 mg/L IBA twice a week for one month. The results showed that IBA at 0.50 mg/L provided the most appropriate concentration for immediate root induction and growth of Dendrobium hybrid planted on coco-husk. Root number (1.75) and root length (0.28 cm) showed the highest and the most important indicator of adventitious root induction